1998
DOI: 10.1016/s0014-5793(98)00363-9
|View full text |Cite
|
Sign up to set email alerts
|

Direct formation of mixed micelles in the solubilization of phospholipid liposomes by Triton X‐100

Abstract: The vesicle to micelle transition which results in the interaction of the Triton X-100 surfactant with phosphatidylcholine vesicles was studied by means of dynamic light scattering (at different reading angles) and by freeze-fracture electron microscopy techniques. Vesicle solubilization was produced by the direct formation of mixed micelles without the formation of complex intermediate aggregates. Thus, vesicle to micelle transformation was mainly governed by the progressive formation of mixed micelles within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
116
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 162 publications
(134 citation statements)
references
References 18 publications
16
116
0
2
Order By: Relevance
“…According to Lopez et al the entrapment of drug occurs both in the bilayer and in the aqueous compartment of the vesicle, for which both surfactant and lipids are responsible. 28 When the lipid compartment and the aqueous phase become saturated with the drug, the vesicle provides limited entrapment capacity. 29 SDC, with a steroidal structure and two OH groups, was used as a surfactant in this study.…”
Section: Mathematical Modelling For Rsm Optimizationmentioning
confidence: 99%
“…According to Lopez et al the entrapment of drug occurs both in the bilayer and in the aqueous compartment of the vesicle, for which both surfactant and lipids are responsible. 28 When the lipid compartment and the aqueous phase become saturated with the drug, the vesicle provides limited entrapment capacity. 29 SDC, with a steroidal structure and two OH groups, was used as a surfactant in this study.…”
Section: Mathematical Modelling For Rsm Optimizationmentioning
confidence: 99%
“…It is well known experimentally that detergents can dissolve lipid membranes into small micelles. 13,[18][19][20][21] Nomura et al 21 observed several types of dynamical behaviors in the lysis of liposomes: opening up by pore formation, inside-out inversion, burst, and vesicle shrinkage with oscillations. Pore-opening and rupture of vesicles were also observed under positive surface tension induced by adhesion to a surface, 22 optical illumination, 22,23 or micropipette aspiration.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the sugar-type and the oxyethylene-type nonionic surfactants have been widely used for this purpose, and thus the nonionic surfactant-induced transition from phospholipid vesicles to micelles has been well studied [2][3][4][5][6][7][8][9][10][11]. Although studies using anionic [12][13][14][15][16][17], cationic [12,18], and zwitterionic surfactants [19] have also been published, they have received less attention.…”
Section: Introductionmentioning
confidence: 99%